MUX: Algorithm Selection for Software Model Checkers - Tulsian, Varun; Kanade, Aditya; Kumar, Rahul; Lal, Akash; Nori, Aditya (Mining Software Repositories (MSR), 2014)
With the growing complexity of modern day software, software model checking has become a critical technology for ensuring correctness of software. As is true with any promising technology, there are a number of tools for software model checking. However, their respective performance trade-offs are difficult to characterize accurately – making it difficult for practitioners to select a suitable tool for the task at hand. This paper proposes a technique called MUX that addresses the problem of selecting the most suitable software model checker for a given input instance. MUX performs machine learning on a repository of software verification instances. The algorithm selector, synthesized through machine learning, uses structural features from an input instance, comprising a program-property pair, at runtime and determines which tool to use. We have implemented MUX for Windows device drivers and evaluated it on a number of drivers and model checkers. Our results are promising in that the algorithm selector not only avoids a significant number of timeouts but also improves the total runtime by a large margin, compared to any individual model checker. It also outperforms a portfolio-based algorithm selector being used in Microsoft at present. Besides, MUX identifies structural features of programs that are key factors in determining performance of model checkers. This paper thus brings machine learning techniques to aid in effective use of software verification tools.